STUDENT CENTERED; PARADIGMA BARU INOVASI PEMBELAJARAN - Wiwik Wijayanti (MAJALAH ILMIAH PEMBELAJARAN, 2011)
School have seemed to proceed as though there were one standardslassroom situation suitable for all students: one textbook, one method,or one curriculum program. School should start with very differentassumption that individual students need very different type andqualities of instruction and require various types of aid, such as groupstudy, tutorial help, or variation in instructional materials that rangebeyond textbooks to acwide variety of printed and audiovisual material,academic games and so on. These are Student Centered Learning, aninstruction which suitable for individual different. Another variable isthe degree of perserverence of the learner. If he find his effort and feelsuccess in learning, his perserverence increase. Motivation is soimportant and so complex that teachers are well advised to seek out andemploy differentiated teaching techniques tailored to individual studentand designed to produce positive results.